Product of distributions and the zero-pressure gas dynamics system (The São Paulo Journal of Mathematical Sciences, 2013)
In this survey article, we discuss a few applications of three successful notions of the product of distributions (the Colombeau algebra, the method of weak asymptotics and the notion of paths) with regard to the zero-pressure gas dynamics system and the associated adhesion approximation. It is shown that the three notions are closely related atleast in the case of one dimensions.